Induced pluripotent stem cells inhibit bleomycin-induced pulmonary fibrosis in mice through suppressing TGF-β1/Smad-mediated epithelial to mesenchymal transition - Yan Zhou; Zhong He; Yuan Gao; Rui Zheng; Xiaoye Zhang; Li Zhao; Mingqi Tan (Frontiers Media S.A., 2016)
Pulmonary fibrosis is a progressive and irreversible fibrotic lung disorder with high mortality and few treatment options. Recently, induced pluripotent stem (iPS) cells have been considered as an ideal resource for stem cell-based therapy. Although an earlier study demonstrated the therapeutic effect of iPS cells on pulmonary fibrosis, the exact mechanisms remain obscure. The present study investigated the effects of iPS cells on inflammatory responses, transforming growth factor (TGF)-β1 signaling pathway, and epithelial to mesenchymal transition (EMT) during bleomycin (BLM)-induced lung fibrosis. A single intratracheal instillation of BLM (5 mg/kg) was performed to induce pulmonary fibrosis in C57BL/6 mice. Then, iPS cells (c-Myc-free) were administrated intravenously at 24 h following BLM instillation. Three weeks after BLM administration, pulmonary fibrosis was evaluated. As expected, treatment with iPS cells significantly limited the pathological changes, edema, and collagen deposition in lung tissues of BLM-induced mice. Mechanically, treatment with iPS cells obviously repressed the expression ratios of matrix metalloproteinase-2 (MMP-2) to its tissue inhibitor -2 (TIMP-2) and MMP-9/TIMP-1 in BLM-induced pulmonary tissues. In addition, iPS cell administration remarkably suppressed BLM-induced up-regulation of pulmonary inflammatory mediators, including tumor necrosis factor-α, interleukin (IL)-1β, IL-6, inducible nitric oxide synthase, nitric oxide, cyclooxygenase-2 and prostaglandin E2. We further demonstrated that transplantation of iPS cells markedly inhibited BLM-mediated activation of TGF-β1/Mothers against decapentaplegic homolog 2/3 (Smad2/3) and EMT in lung tissues through up-regulating epithelial marker E-cadherin and down-regulating mesenchymal markers including fibronectin, vimentin and α-smooth muscle actin. Moreover, in vitro, iPS cell-conditioned medium (iPSC-CM) profoundly inhibited TGF-β1-induced EMT signaling pathway in mouse alveolar epithelial typeⅡcells (AECⅡ). Collectively, our results suggest that transplantation of iPS cells could suppress inflammatory responses, TGF-β1/Smad2/3 pathway and EMT during the progression of BLM-induced pulmonary fibrosis, providing new useful clues regarding the mechanisms of iPS cells in the treatment for this disease.